Free Akivis algebras, primitive elements, and hyperalgebras (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Free Akivis algebras and primitive elements in their universal enveloping algebras are investigated. The conjecture of K .H . Hofmann and K. Strambach on the structure of primitive elements is proved to be not valid, and a full system of primitive elements in free nonassociative algebra is contructed.